GAMBARAN FAKTOR RISIKO TEKANAN DARAH SISTOLIK PADA PEKERJA TAMBANG BATU KAPUR DI KLAPANUNGGAL, BOGOR, JAWA BARAT - ANNISA WARDA IRVANI (Majalah Kedokteran Andalas, 2020)
Hypertension is a disease that often lead to patient death as it does not have specific symptoms. The high prevalence in Bogor Regency caused by minimal health facilities, so there was no guarantee of occupational health for workers and the workers lack of knowledge. Objective: To determine the risk factors that affected systolic blood pressure in limestone miners in Klapanunggal. Method: Uses observational analytic study with cross sectional design with a total of 47 people. Result: The measurement of noise intensity are 83.2 dB on a breaker and 91.7 dB on a stone crusher. The average systolic blood pressure before and after work was 110.28 mmHg and 126.23 mmHg. The results of one-way ANOVA test, a correlation between noise intensity, working period, prolonged exposure, and smoking habits with systolic blood pressure with p=0.001 was obtained. According to dummy regression test, noise intensity were the most influential. Workers exposed to noise with an intensity normal had an average increase 10.45 mmHg, while those exposed to an intensity abnormal 22.27 mmHg. Conclusion: Noise intensity, working period, prolonged exposure, and smoking habits affect systolic blood pressure and the most influential factor was noise intensity.